Nursing Work Arrangement in Health Care Settings During the Pandemic Of Covid-19: Nurse Managers’ Perspectives - Nurfika Asmaningrum; Kholid Rosyidi Muhammad Nur; Retno Purwandari; Anisah Ardiana (NurseLine Journal, 2020)
Nurses are health service providers playing pivotal role and serving at the forefront of tackling COVID-19. As such, their health and safety are pivotal. Therefore, a policy is needed in arranging their work system in response to COVID-19 pandemic. The work arrangement denotes an effort to prevent human-to-human infection transmission of COVID-19. However, the nursing work system adjustment model is not yet know. The aim of the study is to explore a model for adjusting the work system of nurses in health care facilities during the COVID-19 pandemic, from the perspective of nurse managers. This study applied descriptive qualitative method. It involved 9 (nine) managers who were recruited from 2 (two) public hospitals which became the national reference for handling COVID-19. These subjects were chosen using purposive sampling technique. Data collection employed semi-structured interviews through virtually telephone and conference. Resultant data was analyzed using content analysis. The study has unraveled five main categories related to the adjustment of the nursing work system during the pandemic, including the management of nurse personnel, regulation at work, arrangement of work patterns, adjustment of work procedures, and flexibility of work systems. Through the work system regulation, hospital managers have implemented the principle of maintaining health, safety and security of nurses while working in health care facilities. The adjustment of the nursing work system aims to reduce the negative impact of the health crisis and reduce anxiety for nurses. This is mainly because the level of anxiety associated with COVID-19 may pose adverse effects on nurses’ wellbeing.